Worst pattern of invasion - type 4 (WPOI-4) and Lymphocyte host response should be mandatory reporting criteria for oral cavity squamous cell carcinoma: A re-look at the American Joint Committee of Cancer (AJCC) minimum dataset - Deval Parekh; Prachi Kukreja; Indranil Mallick; Paromita Roy (Wolters Kluwer Medknow Publications, 2020)
Background: A proportion of early-stage node-negative oral squamous carcinoma patients fail despite complete surgical resection. Adjuvant treatment in early oral cancer is controversial and is often individualized based on stage, depth, and margin status. Aims: We reviewed various histological markers in pT1/T2N0 cases, resected upfront with elective nodal dissection, with an emphasis on tumor-tissue interface characteristics of the worst pattern of invasion (WPOI), tumor cell nest size (sCNS), budding and lymphocytic host response (LHR), to assess their prognostic significance. Materials and Methods: Archived blocks of 95 cases were reviewed. Tumor stage, grade, size, depth of invasion, lymphovascular, and perineural invasion, WPOI, LHR, sCNS, and tumor bud (single cells or <5 cell clusters) score were recorded. Statistical Analysis: Prognostic significance was statistically analyzed using SPSS software version 20. Results: Depth of invasion (P = 0.008), WPOI- 4 and 5 (P = 0.033), sCNS (<5 cells) at tumor interface (P = 0.010), high bud count (≥3 buds/40 × hpf) (P = 0.021) and poor LHR (P = 0.019) correlated significantly with poor disease-free survival on univariate analysis. However, on multivariate analysis only LHR and WPOI-4 (that is presence of small cell nests or buds) were significant, with high hazard ratio of 4.351 (95% CI 1.290-14.676, P = 0.018) and 5.019 (95% CI 1.212-20.789, P = 0.026), respectively. Conclusion: We propose mandatory reporting of WPOI-4 at the tumor interface and absence of LHR, as significant markers of poor prognosis in early-stage oral cavity squamous carcinoma.